Technical and anatomical aspects of endoscopically assisted septostomy in unilateral ventriculoperitoneal shunt placement for the management of isolated lateral ventricles - Mohammad H. Mohammad, MD; Roberto Jose Diaz, MD, PhD, FRCSC (Interdisciplinary Neurosurgery, 2017)
Background: Isolated lateral ventricle is a specific form of non-communicating hydrocephalus that is caused by an obstruction of the foramen of Monro. The condition was previously treated with bilateral shunt placement. However, the emergence of endoscopic surgery has provided more options in the management of this condition. Case description: 46-year-old female presented with obstructive hydrocephalus caused by a right thalamic primary central nervous system B-cell lymphoma. Endoscopic septostomy with unilateral shunt placement was performed because of bilateral foramen of Monro obstruction. Conclusion: Endoscopic septostomy can be used as a tool to avoid bilateral shunt placement in certain cases of bilateral isolated lateral ventricles. Keywords: Septostomy, CNS lymphoma, Endoscopic surgery, Isolated ventricles